Ammonium ionic liquids as green solvents for drugs - Melo, Catarina I. (2014)
A high solubility of antituberculosis antibiotic drugs: isoniazid and pyrazinecarboxamide in ammonium ionic liquids shown in this work, demonstrates the promising perspectives in the drug processing. Solid–liquid equilibrium (SLE) measurements have been made using a dynamic (synthetic) method. Thermophyscial properties such as melting point, enthalpy of fusion, temperatures of phase transitions and corresponding enthalpies for both isoniazid and pyrazinecarboxamide as well as for three ammonium salts were acquired using differential scanning calorimetry (DSC). The solubility of isoniazid in analysed ILs was found to be higher than that of pyrazinecarboxamide. Considering ammonium salts examined in this work, didecyldimethylammonium nitrate is the best solvent for both antibiotics. The solid–liquid phase equilibria were described using six different correlation equations which revealed a relatively good description with an acceptable standard deviation temperature range.